A comparative analysis of transformation between local and global media and advertising agencies in South Africa - Ndinguri, Kevin (University of the Witswatersrand, Johannesburg, 2023)
Poverty, unemployment and inequality among black people have been identified as key consequences of apartheid. To redress these, the Broad-Based Black Economic Empowerment Act was enacted. In the Media and Advertising industry in South Africa, the B-BBEE Act is translated through the Media and Communications Charter (MAC) which describes five elements, namely; management inclusion, skills development, responsible advertising, preferential procurement and socio-economic development. Most of the media industry studies on the compliance to the MAC charter focus on descriptions of how companies have applied the B-BBEE Act. This study’s specific objectives were to describe the nature of transformation in local media and advertising agencies, describe the nature of transformation in global media and advertising agencies and describe the effect of B-BBEE codes on local and global media and advertising agencies in South Africa. The study used a qualitative approach and an exploratory-descriptive design. The data collection tool was semi-structured interviews and data was collected through in-depth interviews. Data were analysed using thematic content analysis and presented in narrative format.The study found four themes that compare the transformation of local and global media and advertising agencies. The first theme is that transformation has taken place in local media agencies, the second is that few transformation initiatives have taken place in global media companies. The third theme is that B-BBEE codes have enabled local media companies to secure clients and the fourth theme is that B-BBEE codes have obligated global media agencies to transform the way they manage their businesses. In conclusion, global media and advertising agencies have been affected by transformation through increased diversity and change in the way they managed their businesses. Recommendations for future research should use a quantitative approach to enable the generalisation of findings
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Business Administration
Keywords: Transformation; Media and advertising; B-BBEE; UCTD; South African media; SDG-9: Industry, innovation and infrastructure